Role of the Conference of the Episcopate of Poland in the Holy See negotiations with the authorities of Polish People's Republic in the second half of the seventies of the 20th century - STĘPIEŃ, MAREK (Prawo Kanoniczne, 2019)
In the first months of 1971 the Government of the Polish People's Republic decided to start talks with the Holy See on the normalization of relations between the State and the Catholic Church. The intention of the Holy See was to achieve recognition of the legal personality of the Church in Poland. The only result achieved however was the will to continue negotiations in the future. Under the Protocol signed by the parties in July 1974, the communist authorities immediately appointed the head of their Team of representatives and began to reside in Rome. The decision to send a permanent representative of the Holy See to Warsaw was first made by Pope Paul VI in 1976 and upheld by John Paul I. After the pontificate began by John Paul II, the position of the Holy See in this matter was modified and as a consequence no delegate of the Pope was sent to the end of the seventies of the last century to Warsaw and no agreement was reached. At every stage of the negotiations that were carried without any representative of Polish Church. Cardinal Stefan Wyszyński, as the Head of the Conference of the Episcopate of Poland, was kept informed about their course and he supported the negotiators by submitting systematically in writing the opinion of the Conference of the Polish Episcopate to the Pope Paul VI, to Pope John Paul II as well as and for the Archbishop Agostino Casaroli. All suggestions and remarks were very valuable and supportive in negotiations due to the fact that they were originated by Polish bishops who knew well the internal situation in the country as well as the way of proceedings of communist authorities.